BOIMPY: Fluorescent Boron Complexes with Tunable and Environment‐Responsive Light‐Emitting Properties. Issue 48 (18th October 2016) - Lee, Boran; Park, Byung Gyu; Cho, Wansang; Lee, Ho Yong; Olasz, András; Chen, Chun‐Hsing; Park, Seung Bum; Lee, Dongwhan
Abstract: A series of air‐stable boron complexes1 –5 were prepared by using N ‐aryl iminopyrrolide ligands. Designed as minimalist structural mimics of the privileged BODIPY motif, these new BOIMPY (BOron complexes of IMinoPYrrolide ligands) fluorophores feature low molecular symmetry that promotes emission from CT‐type excited states with large Stokes shifts and little self‐quenching. Through comparative studies on the homologous set of compounds1 –4, we have confirmed that a delicate interplay between conformational twisting and donor–acceptor interaction dictates the mechanism of de‐excitation, which responds sensitively to solvent polarity as well as protonation states. Over a wide visible spectral range, the structure‐dependent light‐emitting properties of BOIMPY molecules are well manifested, even in the solid‐state. In order to exploit the environment‐sensitive nature of CT‐type emission, the BOIMPY motif was elaborated further into a bioprobe molecule5 . Live‐cell fluorescence imaging studies have established that5 is localized exclusively at lipid droplets to produce well‐resolved staining patterns without affecting cell viability. These findings promise future elaboration of BOIMPY‐based functional molecules for applications in biological imaging, chemical sensing, and molecular switching. Abstract : Desymmetrized light‐emitters : Air‐stable boron complexes of π‐conjugated N, N ‐bidentate ligands promote emission from charge‐separated excited states with large Stokes shifts and little self‐quenching, which allow for solid‐state emission and live‐cell fluorescence imaging (see figure).